Preparation and Characterization of Topical NIOSOMAL Gel for Acne Treatment - Vasam, Mallikarjun (Asian Journal of Pharmaceutics (AJP), 2024)
Acne is a widespread skin condition that usually impacts individuals at some point in their lives. The structure of the stratum corneum is often likened to a brick wall, with corneocytes surrounded by intercellular lipid lamellae acting as the mortar. Using elastic vesicles (niosomes) that can be transported through channel-like structures in the skin is a highly efficient approach for delivering drugs to the affected area of the skin. This study utilized niosomes as a delivery system for a combination of adapalene and benzoyl peroxide (BPO). The aim was to effectively treat acne by targeting the site of infection. Within this section, the evaluation of drugs enclosed in a niosomal gel formulation was conducted to determine their specific characteristics through in vitro and ex vivo testing. The drug content in niosomal gel formulation F2 is 91.11%, in F6 is 94.21%, and in F8 is 96.99%. The total percentage of drug release from formulations containing ordinary adapalene gel (F8) was 99.27%. The release kinetics of the chosen niosomal gel were precisely regulated through diffusion, specifically following the Higuchi model. In a span of 24 h, the niosomal gel allowed for a precise permeation of 6.25 ± 0.14 g/cm2 of adapalene, whereas the permeation of BPO amounted to 5.04 ± 0.014 g/cm2. Furthermore, the niosome gel’s stability was assessed at various temperatures to identify the necessary storage conditions for preserving the quality of the formulation